The content of melamine in milk based products, and milk powders analyzed by liquid chromatography mass spectrometry - S, Rachmawati; PM, Widiyanti (Indonesian Journal of Animal and Veterinary Sciences, 2013)
Melamine is a white crystal of organic compound has a molecular weight of 126.12, difficult to solve in water. Cases of illegally adding melamine in milk powder is subjected to increase the nitrogen content of milk, because melamine contains high nitrogen (66%), so when milk is tested, seems contains high protein. This paper presented data the content of melamine in products based milk, and milk powders which entered and marketed in Indonesia. Melamine analysis is done by LC- MS 2010 EV, Shimadzu. Confirmation and validation tests indicate that melamine scanning found at m/z = 127, suitable system of analysis with relative standard deviation (RSD) given of 1,18% (< 2,0%). Accuracy test gave the average of 89.1% recovery, detection limit of 5 ppb and limit of quantition 7 ppb. About 91.3% samples (n = 46) collected from animal quarantine Tanjung Priok contained melamine in the range of 6.7 ppb to 61.5 ppb which is 1/49 to 1/16 times less than standard limit. Whereas about 40%, 14 out of 35 samples collected from Bandung and Jakarta supermarket was not detected of melamine, and 60% samples positive contain melamine in the range of 5,1 to 26,5 ppb (1/200 to 1/38 standard limit). However, all the samples analyzed contain melamine below the standard limit of 1 ppm determined by WHO/FAO. Key Words: Melamine, Milk Powder, Milk Based Products, LCMS